Pemukiman Kumuh Bantaran Sungai Deli Kelurahan Labuhan Deli Medan Sumatera Utara - Syahril Ginting; Ibnu Hajar; Usman Pelly (Universitas Negeri Medan, 2019)
This paper is part of the Unimed Anthropology Social research thesis which aims to explain the development of slum settlements on the Deli river and find ways to rejuvenate the Deli riverbank without involving social conflict. This study uses ethnography method. Research technique with interviews conducted and observations of informants in the Deli river in Labuhan Deli Village. From the results of the research, the people come from various regions in North Sumatra, such as Karo and Langkat Regencies, migrated to Medan for improve their lives, but lost because they did not have education and skills. The existence of a culture of fear of returning home because they had migrated, so they continued to live in the city of Medan, there was no other way but to find cheap settlements to survive, one of which was by arranging the river banks of the Deli. The government must issue policies that regulate settlers to settle in more feasible places, namely: with relocation programs, socialization of appropriate education and the dangers of settling in slums. Therefore, with this policy the community has new settlements, where these settlements have low installments and are pioneered by the government.